(untitled) (American Journal of Islam and Society, 2009)
Parin Dossa’s book on the lives of Canadian Muslims provides insight into the personal stories of women who must grapple with disability in their daily lives. It is, therefore, located at the intersection of race, gender, and disability studies and has broad social implications. In her introduction, Dossa discusses the 1967 change in Canadian immigration policies that made immigration easier for a pool of skilled laborers needed to fill jobs in the economy. Though this search for skilled labor is posited as objective, these policies are biased as regards the relative value of different bodies. Disabled bodies are valued less in this system. Racial biases make the situation of racialized disabled people even more difficult. Dossa’s project seeks to investigate the experience of a racialized body in a world that disables. To counter this external lack of value, the women featured create an alternative space of self-value through storytelling ...